Notice of Joint Meeting and the Oxnard and Camarillo Master Plans March 3, 1996 - Rodney L. Murphy:::::: (1996)
The agenda for a joint meeting between Camarillo and Oxnard Airport Authorities and the Aviation Advisory Commission. Includes a letter discussing the master plans of Oxnard and Camarillo sent by Rodney L. Murphy the Director of Airports.